Penuangan Checks and Balances kedalam Konstitusi - Chandranegara, Ibnu Sina (Jurnal Konstitusi, 2016)
On Research “checks and balances” in legal studies often raises high quality questions such as, does the checks and balances is a doctrine, principle, or legal theory, or maybe precisely the formula of power in politics. History been recorded, that in any discussions regarding the formation of the constitutional separation, division and smelting power is something that is popular to be discussed before and even after becoming the constitution. Therefore, the casting of checks and balances into the constitution is an interesting study to determine the portion and posture.